Conceptions of the Nature of America: from the Discovery to the Enlightenment - Serna Arnaiz, Mercedes (Anales de Literatura Hispanoamericana, 2010)
The centuries of the discovery and conquest were characterized by a providentialist vision of history which had a direct impact on the concept of the nature of America and underpinned the historiographical writing of the period. From the eighteenth century onwards, the mystical- geographical concept that Christianity had imposed on terrestrial geography began to fade away. Indeed, the naturalists, historians and philosophers of the eighteenth century sought to study the nature of America in a more objective way and to provide a more systematic structure for knowledge. As a result, the Chronicles of the Indies fell into discredit. However, this new approach to the reading of the chronicles reflects not just a desire to use more reliable sources of evidence, but also a specific political agenda, embodied in the creation of the leyenda negra.
Keywords: Chronicles; Nature of America; Enlightenment; Climate of America; Civilization